Research correlation between wastewater indicators for operational control - Shatokhina, Y.; Kovalev, O. (Energy and Automation, 2015)
On the basis of studies of waste water. Slavutich developed image depends determining COD and suspended solids concentration by transparency for operational control of the cleaning process.